Structure and internal organization of overcharged cationic-lipid/peptide/DNA self-assembly complexes - Yan, Jiang (2013)
The combination of cationic lipids with cationic peptides and DNA vectors can produce synergistic effects in gene delivery to eukaryotic cells. Binary complexes of cationic lipids with DNA are well-studied whereas little information is available about the structure of the ternary lipid/peptide/DNA (LPD) complexes and mechanisms defining DNA protection and delivery. Here we use synchrotron small angle X-ray scattering and dynamic light scattering zeta-potential measurements to determine structure and the net charge of supramolecular aggregates of complexes in mixtures of plasmid DNA, cationic liposomes formed from DOTAP, plus a linear cationic ε-oligolysine with the pendant α-amino acids Leu-Tyr-Arg (LYR), ε-(LYR)K10. These ternary complexes display multilamellar structures with relatively constant separation between DOTAP bilayers, accommodating a hydrated monolayer of parallel DNA rods. The DNA–DNA distance in the complexes varies as a function of the net positive to negative (lipid + peptide)/DNA charge ratio. An explanation for the observed dependence of DNA–DNA distance on charge ratio was proposed based on general polyelectrolyte properties of non-stoichiometric polycation–DNA mixtures.